Encephalitis after influenza and vaccination: a nationwide population-based registry study from Norway. (27th July 2017) - Ghaderi, Sara; Størdal, Ketil; Gunnes, Nina; Bakken, Inger J; Magnus, Per; Håberg, Siri E
Abstract: Background: Influenza is known to be associated with various neurological complications, including encephalitis. We conducted a registry-based study to assess the risk of encephalitis after influenza and A(H1N1)pdm09 vaccine. Methods: Data from Norwegian national health registries during 2008–14 were linked using the unique personal identifiers given to all Norwegian residents ( N = 5 210 519). Cox proportional-hazard models with time-varying variables were fitted to estimate hazard ratios (HRs) of encephalitis after influenza and A(H1N1)pdm09 vaccine, using the risk windows 0–7, 0–14, 0–30, 0–60, 0–90 and 0–180 days. Results: In Norway, 684 172 individuals received an influenza diagnosis and 2793 patients were hospitalized with encephalitis during 2008–14. The risk of encephalitis increased after influenza: HR, 7-day risk window: 47.8 (95% confidence interval (CI): 35.8–63.8), and the HR decreased for longer risk windows; HR, 180-day risk window: 3.8 (95% CI: 3.1–4.7). HR of encephalitis after influenza during the 2009 main pandemic wave using a 7-day risk window was 30.0 (95% CI: 10.8–83.2). We found no differences in the risk of encephalitis after the seasonal influenza compared with influenza during the 2009 main pandemic wave; HR, 7-day risk window: 1.3 (95% CI: 0.4–4.3). A(H1N1)pdm09 vaccine was not associated with the risk of encephalitis: HR, 14-day risk window: 0.6 (95% CI: 0.2–2.1). Conclusions: There was an increased risk of encephalitis following influenza but not after A(H1N1)pdm09 vaccine. The risk of encephalitis was highest in the first few weeks after influenza.